Traditional food blunders: kuih bahulu losing its authentic touch / Amirul Hakim Zulkifli ... [et al.] - Zulkifli, Amirul Hakim; Wan Ismail, Wan Rusni; Hashim, Nurul Huda; Marzuki, Marzlin (2018)
Bahulu, a small traditional Malay cake has successfully made their way into the mainstream local snacks that is available all year round and no longer labelled as a seasonal snack that is only popular during the Eid celebration. Such changes is a positive indication that the younger generations are still interested with this traditional snack. To meet with the current demand, bahulu producers has made certain changes on the formula of this so call traditional snack in order to mass produce this product at the lowest cost as possible. Apart from that, the traditional ways of preparing bahulu using coconut husks as a fuel is no longer feasible as the majority of bahulu today that are sold in the supermarket are freshly baked from the oven. The use of machinary and changes in the formulation in current production has changed this traditional snack characteristics, thus endangering bahulu of losing its traditional identity. Therefore this study was carried out to investigate whether consumers especially the younger generations were able to differentiate between the traditional and modern bahulu. Sensory evaluation is used in this study to test for consumers perception on the characteristics of traditional bahulu based on five senses of smell, taste, sound, touch and sight. A total number of 30 untrained panelists are used in this study using randomized double-blind procedures in order to overcome problem related with artifact due to order presentation. All samples were arranged and labeled in three digits code number from score cards were decoded. Then, the score for each and every sample are analysed using ANOVA to compare their significance mean score, followed with Tukey-HSD test for the post-hoc test. Result obtained was, bahulu in which formula a sponge -like texture were recorded as the highest rank among the other five samples. Bahulu are losing its authentic touch as the consumer's perception and preferences on bahulu's unique characteristics tend to change overtime.